Stakeholders’ Perception of Sustainability in Educational Buildings in Nigeria - Aghimien, Douglas Omoregie; Awodele, Oluwaseyi Alabi; Aghimien, Emmanuel Imuetinyan (International Journal of Sustainable Construction Engineering and Technology, 2018)
Building plays a vital role in the delivery of quality education. It is therefore necessary to provide not just buildings but sustainable ones, since educational buildings are meant to serve both the present generation and generations to come. This paper presents the findings of the assessment of sustainability in educational buildings in Nigeria from the stakeholders view point. A survey design approach was adopted and questionnaire was administered on construction participants in selected higher institutions. Data gathered were analyzed using percentage, relative importance index, and Kruskal-Walis H-test. The study revealed that sustainability in educational buildings in the country is on the average with the social dimension ranking a bit higher than the economic and environmental dimensions. There is also a significant divergence in the view of construction stakeholders as to the sustainability features of educational buildings. This divergence tends to affect the priority placed on sustainability as some critical sustainability features such as thermal, visual and acoustic comfort, needed for sustainable educational buildings were found to be very low. If this is to change, then more orientation of construction stakeholders as regards sustainability is needed. The study therefore recommends that educating construction participants, on the concept of sustainability is necessary in order to improve the understanding of sustainability among participants, and achieve sustainability in its holistic form. The study contributes to the body of knowledge as it brings to light the sustainability nature of educational buildings in the country from the stakeholders’ perspective; an aspect that has lacked research attention in the discussion of sustainable construction in the country. It is therefore believed that its findings will assist those responsible for the delivery of educational buildings across the country in delivering sustainable buildings for effective learning.